Праздник Букваря: стихи и рассказы / [худож. Н. Беланов и др.] (Астрель [и др.], 2008)
Экземпляры: Ч/з ДБ (20091019) / Инвентарный номер: 95218 / Цена: 69.50 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 68 / ББК: 84(2Рос=Рус)6